The Accuracy of Endometrial Sampling and Clinical Affecting Factors as a Predictor of Final Surgical Pathology in Endometrial Cancer - Lukkana Promwattanaphan; Sikarn Satitniramai (Clinical and Experimental Obstetrics & Gynecology)
Background: We conducted a retrospective study to evaluate the correlation between preoperative and final histologic diagnoses of endometrial cancer and to identify clinicopathologic factors associated with the concordance between initial and final hysterectomy specimens. Methods: Patients who underwent primary surgical treatment for endometrial cancer at our institute from January 2016 through December 2020 were enrolled. The International Federation of Gynecology and Obstetrics (FIGO) grade and histologic subtype in the pathologic reports were recorded. The level of agreement of tumor grade and histologic type were analyzed. Results: A total of 425 cases were recruited. The overall level of agreement between preoperative grading was moderate according to kappa statistics (κ = 0.469, 95% confidence interval [CI]: 0.385, 0.553). Furthermore, agreement related to the histologic subtype was substantial (κ = 0.778, 95% CI: 0.682, 0.874). The most frequently used endometrial sampling methods were the office endometrial sampling and endometrial curettage (49.2% and 32%, respectively). Among each diagnostic method, manual vacuum aspiration and endometrial curettage had high tumor grade correlation between the preoperative sampling and final pathology (κ = 0.743, 95% CI: 0.549, 0.937 and κ = 0.624, 95% CI: 0.512, 0.736, respectively). Negative peritoneal cytology was was the significant factor associated with concordance between preoperative endometrial sampling and final surgical pathology, with an adjusted odds ratio (OR) of 2.01 (95% CI: 1.03, 3.92; p = 0.040). Conclusions: Regardless of the different diagnostic methods, preoperative endometrial biopsy has limitations in predicting tumor grade compared with final hysterectomy specimens in women with endometrial cancer.